Inverse coupling in leak and voltage-activated K+ channel gates underlies distinct roles in electrical signaling. - Ben-Abu, Y.; Zhou, Y.; Zilberberg, N.; Yifrach, O. (Nature Structural and Molecular Biology, 2009)
Voltage-activated (Kv) and leak (K(2P)) K(+) channels have key, yet distinct, roles in electrical signaling in the nervous system. Here we examine how differences in the operation of the activation and slow inactivation pore gates of Kv and K(2P) channels underlie their unique roles in electrical signaling. We report that (i) leak K(+) channels possess a lower activation gate, (ii) the activation gate is an important determinant controlling the conformational stability of the K(+) channel pore, (iii) the lower activation and upper slow inactivation gates of leak channels cross-talk and (iv) unlike Kv channels, where the two gates are negatively coupled, these two gates are positively coupled in K(2P) channels. Our results demonstrate how basic thermodynamic properties of the K(+) channel pore, particularly conformational stability and coupling between gates, underlie the specialized roles of Kv and K(2P) channel families in electrical signaling.